Establishing a link between well-ordered Pt(100) surfaces and real systems: How random superficial defects influence the electrooxidation of glycerol? - Fernández, Pablo S. (2015)
Glycerol (GlOH) accumulation and its very low price constitute a real problem for the biodiesel industry. To overcome these problems, it is imperative to find new GlOH applications. In this context,electrochemistry arises as an important alternativeto the production of energy or fine chemicals using GlOH as a reactant. To make these opportunities a reality, it is fundamentallynecessary to understand how the glycerol electro-oxidation reaction (GEOR) occurs on catalysts used in real systems.Thus, research using model surfaces generates the first insight into the electrochemistry of extremely complex real catalysts. Accordingly,in this work, we generate Pt(100) disturbed surfaces in a reproducible manner, carefully controlling the surface defectdensity. Then, GEOR is studied on well-ordered Pt(100) and on the disturbed Pt(100) surfaces in 0.5 M H2SO4 using cyclic voltammetry(CV) and in-situ Fourier transform infrared spectroscopy (FTIR). The CV profile of GEOR consists of a single peak in thepositive scan. The onset reaction displays the influence of defects present on the surface. On a surface with a high degree of disorder,the main GlOH oxidation process begins at 0.8 V vs. RHE, whereas for well-ordered Pt(100), it starts 0.1 V earlier. FTIR experimentsshow the presence of carbon monoxide and carbonyl absorption bands. The electrochemical and spectroelectrochemical results are supported by computational calculations (DFT) showing that both CO and GlOH bind more strongly on disturbed than well-ordered surfaces. Thus, our experiments show that Pt-CO (or other GlOH residue) bond breaking may be the GEOR rate determining step.